Relationship between the Degrees of Severity Sequelae after Treatment with Quality of Life in Patients of Pulmonary Tuberculosis Patients - Deddy Nur Wachid Achadiono; Heni Retnowulan; Tiara Putri Utami (Faculty of Medicine Universitas Gadjah Mada, 2016)
ABSTRACTBackground: Tuberculosis remains a global health problem, especially for developing countries.Tuberculosis can cause permanent deformity of the lung parenchyma, airways, pleura, mediastinum,chest wall, and vascular. This deformity is residual symptoms or sequelae. Tuberculosis sequelae mayoccur in most patients although has completed treatment. These sequelae can affect lung functionand will ultimately influence patient’s quality of life.Objective: This study aims to determine the relationship between the severities of sequelae aftertuberculosis based index Willcox with patient’s quality of life.Methods: The study design was cross-sectional at patients of outpatient clinic BP4Yogyakarta from September 2013 until the samples are met. The relationship between theseverities of the degree of sequelae after treatment with the quality of life in patients with pulmonarytuberculosis will be analyzed using t test. Relationship is significant if p <0.05 with 95% confidenceintervals.Results: The total of the subjects are 37 consist of 24 patients (64.9%) males and 13 (35.1%) women.Subjects who met the criteria will be examined the thoracic x-ray poster anterior (PA). Severity of tuberculosis sequelae will be assessed according to the index Willcox. Subjects also completed a SGRQ questionnaire as a tool for assessing their quality of life. There is a significant correlationbetween the severity of tuberculosis sequelae with the quality of life in the activity (ρ = 0.031) and total (ρ = 0.037) domain.Conclusions: There is a relationship between the severities of the quality of life in patients with pulmonary tuberculosis sequelae.